Indoor production of Brassicaceae microgreens using led light and different light intensities - Ibrahim, Nursyafiqah (2020)
A study was conducted to assess the effect of different regimes of irradiance generated by LEDs with cool white fluorescent (CWF) on the growth and nutritional contents of four species of Brassica microgreens (Chinese kale, Pak Choy, mustard and radish). The objective of this study was to determine the effects of different combination of light quality (red and blue LED with CWF) and intensity (120, 150, 180 and 210 μmol m-² s-1), sowing density and nutrient concentration in influencing growth and phytochemical compound of Brassica microgreens. Light regime had insignificant effect on yield, however, vegetative features such as hypocotyl elongation, cotyledon area and stem thickness varied significantly under different light treatment. While yield was insignificant, combination of red, blue LEDs with CWF (150 μmol m-² s-¹) produced visually pleasing microgreens. Radish produced higher yield and higher concentration of phenolic and flavonoid compound than the other species. In second experiment, effects of light regime and sowing density (3.5 and 7.0 g seeds per container) on radish microgreens were determined. Higher sowing density, produced higher fresh weight due to increase in number of emerging shoots per area in response to higher seeds number, however, individual shoot weight decreased by 15%. Lower sowing density promoted higher individual fresh weight, nutrients, phenolic and DPPH activity. Five levels of nutrients concentration was used (1.0, 1.5, 2.0, 2.5 and 3.0 mS cm-1) in the subsequent study. Results indicated that microgreens fresh weight increased gradually by 6%, 17%, 27% and 31% with increasing concentration (1.5, 2.0, 2.5 and 3.0 mS cm-1) compared to microgreens grown with EC1.0. Total phenolic gradually increase by 28%, 47%, 65% and 81% as nutrient concentrations increased. Flavonoid content was highest when grown using EC2.5 but decreased by 57% when treated with EC 3.0. Nitrate accumulation in microgreens under EC2.5 was lower with 16% reduction compared to EC3.0. In conclusion, light regime did not affect final yield of microgreens, but the distribution of vegetative part of microgreens was largely affected by the combination of light spectrum and intensity. Increased in nutrients concentration with proper sowing rate help to enhance microgreens growth and increased yield.